On rurality - A brief review of the "Rural Development Sociology" collection - Hodžić, Alija (Sociološki pregled, 2017)
This text, both a review and an overview, refers to the notion of rurality, the supporting concept of the collection of papers „Rural Development Sociology”. It points to the complexity and historicity, perception and politics of the social reality that the notion of rurality covers, and to the importance of the Collection for possible rural and regional development policy.
Keywords: recomposition; communications; binary divisions; peasantry; rurality